Internal Gene Cassette from a Genotype S H9N2 Avian Influenza Virus Attenuates the Pathogenicity of H5 Viruses in Chickens and Mice - Hao, Xiaoli; Wang, Jiongjiong; Hu, Jiao; Lu, Xiaolong; Gao, Zhao; Liu, Dong; Li, Juan; Wang, Xiaoquan; Gu, Min; Hu, Zenglei; Liu, Xiaowen; Hu, Shunlin; et al. (Frontiers in Microbiology, 2017)
H9N2 avian influenza virus (AIV) of genotype S frequently donate internal genes to facilitate the generation of novel reassortants such as H7N9, H10N8, H5N2 and H5N6 AIVs, posing an enormous threat to both human health and poultry industry. However, the pathogenicity and transmission of reassortant H5 viruses with internal gene cassette of genotype S H9N2-origin in chickens and mice remain unknown. In this study, four H5 reassortants carrying the HA and NA genes from different clades of H5 viruses and the remaining internal genes from an H9N2 virus of the predominant genotype S were generated by reverse genetics. We found that all four H5 reassortant viruses showed attenuated virulence in both chickens and mice, thus leading to increased the mean death times compared to the corresponding parental viruses. Consistently, the polymerase activity and replication ability in mammalian and avian cells, and the cytokine responses in the lungs of chickens and mice were also decreased when compared to their respective parental viruses. Moreover, these reassortants transmitted from birds to birds by direct contact but not by an airborne route. Our data indicate that the internal genes as a whole cassette from genotype S H9N2 viruses play important roles in reducing the pathogenicity of the H5 recombinants in chickens and mice, and might contribute to the circulation in avian or mammalian hosts.